Analisis Kinerja Sosial dan Keuangan Lembaga Keuangan Mikro (LKM) Usaha Ekonomi Kelurahan-Simpan Pinjam (UEK-SP) Bulan Purnama Kelurahan Padang Bulan Kecamatan Senapelan Kota Pekanbaru - Bobby Irtanto; Ahmad Rifai; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The Reseacrh conducted in Microfinance Institution of UEK-SP Bulan Purnama Padang Bulan Village Senapelan Distric Pekanbaru City. The aim of research is to analysis a social performance and financial performance of Microfinance Institution. The social performance using the MIX Market analysis tool comprised of 16 indicators and measure financial performance analysis tools Pearlscon sistsof 17 ratios. Secondary data obtained by the method of documentation in the form of financial statements from 2009 to 2013 which comprises the balance sheet, loan statements, reports results of operations, the general state of the research and inany other information deemed necessary to supportand complement the data as well as data from related agencies among the research. Social performance of UEK-SP Bulan Purnama has achieved the social and social mission seen is out real and the dept of out reach of IMF, UEK-SP. The financial performance of UEK-SP Bulan Purnama showed that 17 rasio indicator PEARLS There are 8 indicators are in an ideal condition while the 9 indicators of the conditions are not ideal protection Ratios (Protection) (P1,P2), the ratio of out standing loans (E1), Delinquency ratio or Non Perfoaming Loan (A1), the ratio ofnetincome (R12), The ratio of current assets ungenerate (L3), Assets growth (S1) , Loangrowth (S2) and the growth of institutional capital (S6). Keywords: UEK-SP, Social Performance, Financial Performance.